2016
DOI: 10.1016/j.coviro.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crop viruses on wild plants

Abstract: Global land conversion and intensification of agriculture mean that remnant native plant populations are increasingly exposed to crop viruses. What are the consequences for wild plants? In natural unmanaged systems, the key consideration is how crop virus infection influences plant fitness. Field studies of virus effects on wild plant fitness are scant. Approaches include (i) observational studies, (ii) studies of experimental plants with natural infection, and (iii) studies of experimental plants with experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…However, cross-protection between any of the virus species in our study is unlikely, because it requires high sequence homology [81]. Therefore, the most probable explanation of our observed low incidences of mixed infections may be inefficient vector transmission of viruses between the wild plants or between cultivated and wild plants [31] and/or high levels of virus resistance in wild species preventing infection or keeping virus titers at undetectable levels [12, 82]. Furthermore, synergistic or additive effects of multiple virus infections causing severe disease could have eliminated co-infected plants [12, 5, 8386].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, cross-protection between any of the virus species in our study is unlikely, because it requires high sequence homology [81]. Therefore, the most probable explanation of our observed low incidences of mixed infections may be inefficient vector transmission of viruses between the wild plants or between cultivated and wild plants [31] and/or high levels of virus resistance in wild species preventing infection or keeping virus titers at undetectable levels [12, 82]. Furthermore, synergistic or additive effects of multiple virus infections causing severe disease could have eliminated co-infected plants [12, 5, 8386].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, synergistic or additive effects of multiple virus infections causing severe disease could have eliminated co-infected plants [12, 5, 8386]. These effects can vary among populations [12, 87, 88], species [89] and environments [75, 90, 91]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogens have been repeatedly shown to jump between species (Levitt et al, 2013;Li et al, 2011;Malmstrom and Alexander, 2016) and the Deformed Wing Virus (Iflaviridae; DWV) affecting honey bees is no exception (Villalobos, 2016). Recent molecular studies have shown that the DWV may have co-evolved with the European honey bee (Apis mellifera), and the original virus may have been a low prevalence pathogen with many variants and low virulence (Martin et al, 2012;Wilfert et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…SIV in chimpanzees described in Rudicell et al 2010). Growing evidence suggests that crop viruses can reduce fitness of both native and exotic plants in a number of ways (Malmstrom & Alexander 2016). Thousands of examples exist of viruses infecting crops and invertebrates that remained undetected until they were opportunistically sequenced, many of which are only distantly related to previously identified viruses (Roossinck et al 2010;Shi et al 2016).…”
Section: Introductionmentioning
confidence: 99%